Evaluation of Entrepreneurship Program in Bandung City - Irvianti, Essy; Murtaqi, Isrochmani (Journal of Business and Management, 2017)
Abstract. Entrepreneurial activity  is  the  wheel  of  economic development at  local,  regional  and  national  levels. Bandung government has a target to create new entrepreneur in accordance with Middle Term Regional Development Plan (RPJMD) for the period 2013 to 2018. To achieve this target, a new entrepreneurship training program is being held. In order to maximize the program’s impact, continuous improvement on the program is necessary. The key of continuous improvement is to do an evaluation. This study used CIPP Model Evaluation to breakdown the whole program into context, input, process, and product. Each part (context, input, process, and product) consists of data which discuss about it. Each part will have its own evaluation based on the data. The context evaluation assessing needs, problems, and assets in creation of the program. The assessment in input evaluation are strategies, planning, and budgeting. Process evaluation is checking if the program execution runs according to plan by monitoring, document and activity checking. After the program is over, product evaluation started by checking if the goal of the program is achieve or not. The design of this research uses descriptive studies, which means information is collected without adding any perception involved. This research also uses qualitative approach to process the data in order to evaluate the new start- up entrepreneurship program in Bandung city. The result of this study shows that this program has been quite successfully from the context, input and product, although there are still some shortcomings in implementation (process), which need improvement. Keywords: Entrepreneurship, Training program, CIPP Model, Bandung City, EvaluationCategory: Entrepreneurship, Performance Management